2020
DOI: 10.1029/2019jd032237
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical Properties of Generating Cells Over the Southern Ocean: Results From SOCRATES

Abstract: The bulk microphysical properties and number distribution functions (N(D)) of supercooled liquid water (SLW) and ice inside and between ubiquitous generating cells (GCs) observed over the Southern Ocean (SO) during the Southern Ocean Clouds Radiation Aerosol Transport Experimental Study (SOCRATES) measured by in situ cloud probes onboard the NCAR/NSF G‐V aircraft are compared. SLW was detected inside all GCs with an average liquid water content of 0.31 ± 0.19 g m−3, 11% larger than values between GCs. The N(D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 76 publications
4
39
0
Order By: Relevance
“…Cloud top was about 1.5 km for the whole layer, and cloud base at 1 km with some precipitation shafts extending lower. The cloud deck was solid on top, but thin with cellular structure (Wang et al, 2020). Figure 4 is a visible wing camera image of the cloud layer at 410 z just before turning north (58 • S), illustrating it was optically thick.…”
Section: Research Flightmentioning
confidence: 99%
“…Cloud top was about 1.5 km for the whole layer, and cloud base at 1 km with some precipitation shafts extending lower. The cloud deck was solid on top, but thin with cellular structure (Wang et al, 2020). Figure 4 is a visible wing camera image of the cloud layer at 410 z just before turning north (58 • S), illustrating it was optically thick.…”
Section: Research Flightmentioning
confidence: 99%
“…Wang et al (2020) analyzed in situ measurements of cloud top generating cells during the SOCRATES field campaign and found that all cloud top generating cells sampled had SLW at cloud top even at CTTs as cold as −33°C. The ubiquitous presence of SLW at cloud top found in in situ data from Wang et al (2020) is consistent with the remote sensing results herein. Optically thick clouds fully attenuate the HSRL signal limiting phase retrievals beneath cloud top on the high-altitude flight legs, but the retrieval algorithm developed herein allowed for identification of CTP.…”
Section: 1029/2020jd033673mentioning
confidence: 99%
“…The RICE was also used to identify when SLW was present based on voltage changes. Periods with a voltage change of at least 2 mV s −1 indicated the presence of SLW (Cober et al, 2001; McFarquhar et al, 2013; Wang et al, 2020). Cloud liquid water measurements were made at a rate of 1 Hz and were linearly interpolated to 2 Hz to assign liquid water measurements to each column.…”
Section: Data Overviewmentioning
confidence: 99%
See 2 more Smart Citations